Development of a Play-Based Learning Model for Early Grade Elementary School Students - Sembiring, Putri Sari Ulfa; Sari, Rahma Dini Aisyah; Telaumbanua, Putri (Outline Journal of Community Development, 2026)
This community service program aims to improve the quality of learning in early grade elementary classrooms through the implementation of a play-based learning model. The target participants were first- and second-grade teachers at SDN 060839, located at Jl. Danau Singkarak No. 2C. The identified problems included the use of monotonous teaching approaches, low levels of active student participation, and limited use of enjoyable and developmentally appropriate learning media for young learners. Through this program, the service team provided training, mentoring, and simulation sessions on the implementation of a play-based learning model using an integrative thematic approach. The model emphasizes students’ active engagement through educational games, motor activities, and simple interactive media that are easy for teachers to design and apply. The activities were conducted in several stages: initial observation, workshops/training sessions, classroom mentoring, and evaluation of implementation outcomes. The results indicate an improvement in teachers’ creativity in designing play-oriented learning activities and an increase in students’ engagement during the teaching and learning process. The program received positive responses from both teachers and the school principal, who stated that the model effectively creates a more enjoyable and meaningful learning environment for early grade students. It is recommended that this program be expanded to other grade levels to ensure broader and more sustainable impact.